2014
DOI: 10.18869/acadpub.3dj.2.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Study of Upper Airway in Different Antero-posterior Jaw Relationships through Cone Beam Computed Tomography

Abstract: Introduction: This study aims at examining the difference of pharyngeal airways in patients with different occlusion postures, hoping to improve diagnostic methods and provide a stable treatment plan for orthodontic patients. Materials and Methods:The data were gathered through CBCT radiographies of patients from a specialized center for radiology. In each occlusion group according to the performed pilot study, 30 people (90 people in 3 groups of class I, II and III, male and female each) were chosen as the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…It seems that the method of selection of sensitivity value was the main reason for this difference. Dadbin et al ( 16 ) performed airway analysis using Dolphin software and reported larger airway volume in class III patients. Also, they showed that class II patients had smaller airway volume than others.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the method of selection of sensitivity value was the main reason for this difference. Dadbin et al ( 16 ) performed airway analysis using Dolphin software and reported larger airway volume in class III patients. Also, they showed that class II patients had smaller airway volume than others.…”
Section: Discussionmentioning
confidence: 99%